O limite das exculpantes penais: a inexigibilidade de conduta diversa como topos e solução - Menezes, Carlos Alberto (2008)
What we have here is theoretical research that deals with the relation between the theme of the limit of penal exculpates and of the use of undemanding diverse conduct as topoi, taking into consideration the justice of the case itself in a concrete way. The idea is to demonstrate that from this relation it is possible to guarantee the security that penal reason once promised the individual. Independent, equal, free, and yet endowed with reason and subjectivity, the individual that modern reason contemplates is that who made the passage from dependency to liberation thus becoming capable of responsibilities. Conceived this way, he associates himself, on one end to the consensus that generated the State through the way of a social contract and, on the other end, to the penal legality that arose afterwards. In this case and also to justify it, penal law chose to promise judicial security as the main piece of its speech. Such promise would be inferred, at times from the felonies (and from the corresponding arbitrated punishments) as determined and written foresight, and at times from the felony itself as a founded system within a combined action i.e. typical, illegal and culpable. However, the judicial experience shows itself disappointed with such promise. This is what happens in the field of culpability, more specifically with exculpates. Aside from average cases, their insufficiencies (omissions) are evident when demands from material justice articulate themselves with borderline cases. This is how cases are considered, those for which the penal law does not contemplate hypothesis that allow inferring all the consequences of an action in which the individual was not able, because of abnormal circumstances, to take such norms as a source of inspiration. At this point, a problem is established and the solution is found in the concept of undemanding of diverse conduct. Without a defined place in the realms of legality, its usage is sustainable, not because of the penal system, but of the concrete problem in itself and thus it is absorbed as topoi, a category borrowed from the theories of argumentation